Using of oncomarkers in morphological diagnostics of epithelial tumors of thyroid gland - Bondarenko О.О.; Shponka I.S.; Gritsenko P.O. (Морфологія, 2009)
This study is dedicated to research molecular marker’s expression in the differentiated thyroid tumors for prognosis of subsequent clinical course. In this study thyroid tumors were analyzed for NIS, thyroglobulin, galectin-3, p53 expression as well as for proliferation activity (based on Ki-67 expression) depending on the presence of metastases and invasion level. It was identified the prognostic value of each marker of biological properties. The immunophenotypes of thyroid cancers with high risk of tumor dissemination were established. The differential diagnostic marker of follicular tumors was proposed as well. These immunomorphology tumor profile based findings allow to predict the clinical course of thyroid cancer that make possible to separate the groups of patients, which need more careful clinical observing and examination, individualization of treatment as well as group of patients, which may get less invasive treatment methods.